2022
DOI: 10.3390/ma15145012
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional 1,8-Diazafluoren-9-One Aggregates for Green Light Enhancement in Hybrid Biocompatible Media

Abstract: Organic aggregates currently play a prominent role, mainly for their unique optoelectronic properties in the aggregated state. Such properties can be related to the aggregates’ structure and the molecular packing mode. In the literature, we have well-established models of H and J aggregates defined based on the molecular exciton model. However, unconventional aggregates, the most unrecognized forms, have been generating interest among researchers recently. Within unconventional aggregation, aggregation-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…In our previous work, we reported on the tendency of DFO molecules to aggregate [12] and investigated the potential for revealing dactyloscopic traces via such aggregates [11]. Importantly, we demonstrated that the enhancement of fingerprint traces can be achieved through the use of DFO aggregates along with DFO-α-amino acid complexes, which represents a novel approach in the field of forensic science.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In our previous work, we reported on the tendency of DFO molecules to aggregate [12] and investigated the potential for revealing dactyloscopic traces via such aggregates [11]. Importantly, we demonstrated that the enhancement of fingerprint traces can be achieved through the use of DFO aggregates along with DFO-α-amino acid complexes, which represents a novel approach in the field of forensic science.…”
Section: Resultsmentioning
confidence: 95%
“…Based on previous studies on the DFO molecule, we have gained extensive knowledge of its chemical behavior in various environments, including its photophysical [9][10][11][12] and application properties [11]. Our investigations revealed clear distinctions between the DFO monomer molecule, its complex with α-amino acids, and the aggregate formed as the postulated cyclodimer.…”
Section: Explanation Of the Underlying Chemistry Using Computational ...mentioning
confidence: 87%
See 2 more Smart Citations